Enduring exil e the metaphorization of exile in the Hebrew Bible - Halvorson-Taylor, Martien A. (Vetus Testamentum, Supplements, 2011)
During the Second Temple period, the Babylonian exile came to signify not only the deportations and forced migrations of the sixth century B.C.E., but also a variety of other alienations. These alienations included political disenfranchisement, dissatisfaction with the status quo, and an existential alienation from God. Enduring Exile charts the transformation of exile from a historically bound and geographically constrained concept into a symbol for physical, mental, and spiritual distress. Beginning with preexilic materials, Halvorson-Taylor locates antecedents for the metaphorization of exile in the articulation of exile as treaty curse; continuing through the early postexilic period, she recovers an evolving concept of exile within the intricate redaction of Jeremiah's Book of Consolation (Jeremiah 30-31), Second and Third Isaiah (Isaiah 40-66), and First Zechariah (Zechariah 1-8). The formation of these works illustrates the thought, description, and exegesis that fostered the use of exile as a metaphor for problems that could not be resolved by a return to the land- and gave rise to a powerful trope within Judaism and Christianity: the motif of the "enduring exile."